ChemInform Abstract: Dimeric ortho‐Palladated Homoveratrylamine as an Efficient Homogeneous Catalyst for Copper‐Free Sonogashira Cross‐Coupling Reaction. Issue 17 (4th April 2013) - Hajipour, Abdol R.; Rahimi, Hannaneh; Rafiee, Fatemeh
Abstract The thermally stable, oxygen and moisture insensitive title catalyst is successfully applied to the Sonogashira cross‐coupling reaction.